Discarding prospective students from engineering - experiences with an aptitude assessment procedure - Weckenmann, Albert; Kreis, Oliver; Hartmann, Wito; Werner, Teresa (Proceedings of 37th Annual Conference of SEFI. "Attracting young people to engineering. Engineering is fun!", 2009)
Since many years, an extremely high rate of dropouts is to be noticed on engineering study courses. In order to decrease the number of failing students, an aptitude assessment procedure has been established for the bachelor study course of Mechanical Engineering at the University of Erlangen-Nuremberg. The prospective students are assessed regarding the final school grades as well as their personal aptitude for a technical profession. First experiences with the execution and impact of the procedure are discussed in order to be able to improve the executed measure. Thus, on long term, a higher output of qualified engineers shall be achieve
UnivIS-Import:2015-04-16:Pub.2009.tech.FT.FT-QMFMT.discar